The Game of Acting Between Professional and Amateur Actors in Kurdish Feature Films (Raparin Journal of Humanities (RJH), 2025)
One of the most influential signs of the identity of a film is the ability of its actors to design the appropriate acting game for the script, the director's vision the available techniques, that's why the acting; its techniques, its art details, and the work of actors, whether amateur or professional, is the key to the success or failure of films. Therefore, the importance of conducting this research is a scientific, artistic and even moral duty for experts and researchers in the field of cinema in Kurdistan, especially Kurdish cinema faces great challenges in this regard in the cooperation of professional and amateur actors, which has become a prominent and repeated hallmark in it. This research was keen, in three parts: research methodology, theoretical framework and research procedures, to cover a wide area of ​​theoretical backgrounds related to its topic.  Among the conclusions that emerged from it is that amateur actors are more able to express themselves in realistic scenes and natural acting techniques, especially in emotional situations and scenes, and professional actors can follow different and opposite patterns in portraying similar characters. And in the moments when two professional actors with different acting styles meet, or a professional actor and an amateur actor, the technique of (action and reaction) becomes the main game in acting, and amateur actors are more capable of acting the reaction than they are of acting the action itself.